Effects oh the pandemic on Brazilian steel production: Analysis of the competitiveness of national production in relation to China (Research, Society and Development, 2025)
The global steel industry has faced unprecedented challenges due to the COVID-19 pandemic, impacting steel production and demand. In Brazil, there was a significant decrease in production and an increase in idle capacity, while China managed to increase its production in 2020. This study aims to analyze the impacts of the pandemic on Brazilian steel production and its competitiveness in relation to China. The methodology involves a narrative review of the literature and analysis of secondary data, including steel production and consumption reports, as well as academic and government publications. The analysis showed that during the pandemic, steel production in Brazil decreased significantly, while China recovered quickly due to government stimulus policies. The Brazilian steel industry faced high production costs and the need for technological modernization, in addition to logistical and political challenges. In contrast, China has benefited from a robust domestic market and effective policies that have sustained demand for steel. The discussion emphasizes the need for Brazil to adopt new strategies to improve its competitiveness, including investments in technology, energy efficiency and sustainable production methods. Furthermore, it is fundamental to expand into foreign markets and develop supportive policies, such as tax incentives and improvements in logistics infrastructure. In conclusion, the pandemic has revealed the importance of resilience and adaptation. For Brazil, reformulating practices and investing in new technologies will be essential to guarantee the sustainability and growth of the steel industry in the post-pandemic scenario.